Réponses

Meilleure réponse !
2013-01-27T13:47:35+01:00

M = (9x²+30x+25) - (6x²+21x+10x+35)

= 9x²+30x +25 -6x² -21x-10x-35

= 3x²+20x -10

 

(3x+5)(3x+5)-(2x+7)

= (3x+5)(3x+5+2x-7)

= (3x+5)(5x-2)

2013-01-27T13:54:42+01:00

1)  Soit * = le fois

      soit x = l'inconnue

 

M= (3x+5) (3x+5) - (3x+5) (2x+7)

M=3x*3x   +3x*5   +5*3x    +5*5  -  [ 3x * 2x + 3x*7 +5*2x +5 *7

M=    6x²                  +15x      +25    -   [ 6x²     +  21x  +  10x   +  35]

M=    6x²                    + 15x   +25     -  [  6x²   +31 x  + 35 ]

M=   6x²                  +15x     +25     -6x²      -31x    -35

M=   16x  - 10

 

2)

 

M= (3x+5) (3x +5) - (3x+5) (2x+7)

M= (3x+5) - (3x+5+2x +7)

M=(3x+5) - ( 5x + 12 )

 

Et voilà ! =)